Analysis of thin-walled steel beams retrofitted by bonding GFRP stiffeners: Numerical model and investigation of design parameters. (15th December 2017) - Ulger, Tuna; Okeil, Ayman M.
Highlights: A new strengthening technique, SBS, for shear-deficient steel structures is presented. A nonlinear FE model incorporating a debonding cohesive zone material is validated. A parametric study is conducted to develop design recommendations for SBS applications. The use SBS for new construction that is free of transverse welds is investigated. Abstract: Enhancing the load capacity of aged and deficient thin-walled steel structures can be accomplished by increasing member stiffness in buckling prone regions. The literature shows that composite materials have become a major player in retrofitting applications. A new strengthening concept, Strengthening-by-Stiffening ( SBS ), is applied to buckling prone web panels in thin walled steel beams by bonding pultruded glass fiber reinforced polymer (GFRP) sections. The first part of present study is focused on the construction of a finite element (FE) model for accurate simulation of experimentally obtained results. Initial imperfections, material non-linearity, interlaminar fracture law to simulate adhesive debonding, and GFRP rupture or delamination are accounted for in the construction of the FE model. The second part of the study was focused on parametric studies using the validated FE model to investigate different GFRP sizes, contact areas, panel aspect ratio and slenderness of the web panels on steel beam with SBS retrofitting. Results from the parametric study were used to establish some limits to assist in SBS design. Finally, possible use of SBS strengthening method in new construction was investigated by substituting all steel stiffeners with bonded composite GFRP stiffeners for the improvement of fatigue related behavior that is known to start at the weld toes of steel stiffeners.